Sahagún e as festas agrícolas mexica: em busca de um sentido - Valdivia, Karen Alejandra Arriagada (2008)
The method structured by friar Bernardino de Sahagún to describe the ancient rituals of the mexica feasts, reveals a deepest sense behind the enormous compilation of the ancient mexica habits and beliefs done by the Franciscan in his chronicle Historia General de las cosas de Nueva España (General History of the things of New Spain). Once Sahagún considered the ancient mexica feasts as idolatry ceremonies , such descriptions expressed two of the main purposes of the missionary: to know the ancient indigenous ritualistic practices and identify any clue of its survival. On the other hand, the descriptions brought to light the main difficulties that Sahagún faced trying to understand and to translate the diversity, the other, that goes much further than the systematic descriptions of the mexica rituals, the organization of its terms and vocables, and the questions that were part of his questionnaire. They also reflected the complex missionary context which friar Bernardino was inserted and which was reflected in his chronicle. Among the eighteen feasts that took place throughout the mexica solar calendar, we have chosen seven of them, connected to the agricultural cycle and which main elements they remitted to, formed an extremely important group in the native cosmovision: water, rain, corn, hills and fire. They are rituals of the vintenas: I Atlcaoalo; IV Huey tozoztli; VI Etzalcualiztli; XI Ochpaniztli; XIII Tepeílhuitl; XVI Atemoztli e XVIII Izcalli. The purpose of this research is to analyze the method structured by friar Bernardino to describe the rituals of these specific vintenas, which was his path of description and what he would be actually saying